Financial Cooperation between China and CEEC: Development and Prospective - JI YIi; LIU ZUOKUI (Global Economic Observer)
Since the implementation of “16+1 Cooperation”, several financial instruments have been adopted by the Chinese government to strengthen the cooperation between China and the CEE countries, including US$ 10 billion USD Special Credit Line, China-CEEC Investment Cooperation Fund (second phase), Sino-CEE Finance Holding Company Ltd and China-CEE Fund. In addition, many Chinese banks have set up branches in CEE countries. Cooperation with institutions such as the European Bank for Reconstruction and Development has been strengthened, and a China-CEEC Interbank Consortium has been established. To diversify the channels of cooperation, currency swap agreements and RMB clearance arrangements have been signed, and cooperation in the bond market has also be strengthened. The main characteristics of China-CEEC financial cooperation are market-orientation and voluntary participation. In the past six years, achievements have been made, and the implementation of various projects contributed a lot to the “16+1 Cooperation”.